Analysis of Chemical Constituents of the Volatile Oil in the Different Parts of Okra by SPME-GC/MS - Lin, Jian-Bo; Shi, Xiang-Jun; Liu, Hua-Liang; Yuan, Ke (Asian Journal of Chemistry, 2011)
This study reports the chemical constituents of the volatile oil in the okra leaf, flower and seed. The chemical constituents was extracted from the different part of okra by solid phase micro extraction method (SPME). The components of chemical constituents of the volatile oil separated and identified by GC-MS. The relative content of each component was determined by area normalization. Sixty eight components obtained from leaf, flower and seed were identified. Among them, 19 common compounds exist in all the three different parts of okra. The leaf and flower contain 30 common compounds, the flower and seed have 22 and the flower and seed contain 23 common compounds. This study is the first report on the chemical compositions of the oil of different parts of okra. The result can provide reference for further research on the composition of okra volatile oil as well as for the exploration and utilization of it.